Strategiczna analiza firmy Halogen Light Tech metodą SPACE - Hlad, Stanislav (My University, 2012)
Przedmiotem niniejszej pracy jest analiza strategiczna przedsiębiorstwa Halogen Light Tech, metodą SPACE, która jest narzędziem w procesie zarządzania strategicznego na etapie informacyjno – decyzyjnym. W pracy poruszony został aspekt utrzymania wiodącej pozycji lidera przez jednostkę na rynku oświetleniowym, która specjalizuje się głównie w produkcji akcesoriów oświetleniowych dla meblarstwa. Analiza strategiczna pozwoliła na weryfikację strategii na przyszłość.

The issue of the MA thesis is performed strategic analysis of Halogen Light Tech using method SPACE, which is a tool in the process of strategic management at the stage of information – decision – making. The work has been moved maintain leadership aspect of the leader, in the lighting market, which specializes mainly produces lighting accessories for the future industry. Strategic analysis allowed the verification strategy for the future.
Strategic analysis of the Halogen Light Tech company using the SPACE method
Keywords: analiza strategiczna firmy; weryfikacja strategii; metoda SPACE; strategic analysis of company; verification strategy; SPACE analysis